The Use of Heparin during Endovascular Peripheral Arterial Interventions: A Synopsis - Arno M. Wiersema; Christopher Watts; Alexandra C. Durran; Michel M. P. J. Reijnen; Otto M. van Delden; Frans L. Moll; Jan Albert Vos (Scientifica)
A large variety exists for many aspects of the use of heparin as periprocedural prophylactic antithrombotics (PPAT) during peripheral arterial interventions (PAI). This variation is present, not only within countries, but also between them. Due to a lack of (robust) data, no systematic review on the use of heparin during PAI could be justified. A synopsis of all available literature on heparin during PAI describes that heparin is used on technical equipment to reduce the thrombogenicity and in the flushing solution with saline. Heparin could have a cumulative anticoagulant effect when used in combination with ionic contrast medium. No level-1 evidence exists on the use of heparin. A measurement of actual anticoagulation status by means of an activated clotting time should be mandatory.